FORMATION OF NI-CU-PLATINUM GROUP ELEMENT SULFIDE MINERALIZATION IN THE SUDBURY IMPACT MELT SHEET - Keays R.R.; Lightfoot P.C. (My University, 2004)
The Ni–Cu–Platinum Group Element (PGE) sulfide deposits of the Sudbury Structure have provided a major portion of the world’s total nickel production and their host rocks have been the subject of numerous research studies, yet a number of perplexing problems remain to be solved. On the one hand, studies seeking to explain the formation of the Sudbury Structure have now converged on a genetic model which proposes that the Main Mass and Offset Dykes of the Sudbury Igneous Complex (SIC) were produced by crystallization of an impact-generated melt sheet. On the other hand, these models have yet to be fully reconciled with the production of the very large volume of magmatic Ni, Cu, Co, and PGE-rich sulfide mineralization and the associated mafic rock types. This paper explores this problem using new precious metal data from the Main Mass and Offset Dykes. These data are used to understand the relationships between these rocks, and to provide constraints on how the Ni–Cu–PGE sulfide ore deposits fit into the geological evolution of the Sudbury Structure. In the two drill cores selected for study in this project, the Mafic Norite has 1–5 modal percent pyrrhotite plus chalcopyrite, and elevated Ni (40–1000 ppm), Cu (40–1140 ppm), and PGE (1.9–7.8 ppb Pd, 1.8–7.3 ppb Pt); this is overlain by Felsic Norite that contains pyrrhotite, and has a wide range in concentration of Ni (13–257 ppm), Cu (7–328 ppm), and PGE (<0.01–6.4 ppb Pd, <0.01–5 ppb Pt). For a similar range of MgO, the upper portion of the Felsic Norite unit has 5–10 times lower Ni and Cu abundances than within-plate basalts and local crustal rocks, and PGE abundance levels are mostly below analytical determination limits. Stratigraphic studies of other compositional profiles around the SIC demonstrate that this depletion signature of Ni, Cu, and PGE is widespread and developed not only above mineralized embayments and offsets, but also above barren sections of the lower contact of the SIC. The depletion of the upper part of the Felsic Norite in Ni, Cu and PGE is presumably due to equilibration of the magma with magmatic sulfide, and accumulation of this dense sulfide liquid. Results of modeling indicate that the parental magma giving rise to the Mafic and Felsic Norites had initial Ni and Cu contents of ∼210 and 110 ppm, respectively. In addition, Ni, Cu and PGE tenors calculated in 100% sulfide from the Copper Cliff Offset average ∼13% Cu, ∼6% Ni, ∼18 ppm Pd, and ∼19 ppm Pt indicating that these sulfides had formed by fractionation from magmas that contained ∼310 ppm Ni, ∼310 ppm Cu, 18 ppb Pd and 19 ppb Pt. These values are factors of 3 to 5 higher than the Ni, Cu, Pd, and Pt contents of the Onaping Formation with average values of 55 ppm Ni, 48 ppm Cu, and 4.9 ppb Pd as well as the marginal sulfide-poor phase of the Worthington Offset quartz diorite, which has average values of 61 ppm Ni, 59 ppm Cu, 2.8 ppb Pd and 4.0 ppb Pt. Both the Onaping Formation and the marginal quartz diorite are believed to represent the initial composition of a large component of the melt sheet. There is therefore a fundamental problem in reconciling the initial metal contents of the SIC magma as indicated by the marginal phases of the Offset dykes and that of the Onaping Formation with the composition of the SIC magma at the times of formation of the sulfides as indicated by their Ni, Cu and PGE tenors. It is proposed that because the SIC melt sheet was initially superheated with a temperature of 1700 °C, it was able to dissolve ∼5 times as much S as it could at its liquidus temperature of ∼1200 °C. It was also initially composed of an emulsion of mafic and felsic melts (Marsh and Zieg, 1999), which may have formed discrete magma cells. As the temperature of the melt sheet decreased, some of these magma cells became S-saturated and the resultant Ni–Cu–PGE sulfides settled downwards and on reaching magma cells lower in the melt sheet were re-dissolved thereby raising the Ni, Cu and PGE contents of the lower magma cells. It was from these “enriched” magma cells that precipitation of the ore-forming Ni–Cu–PGE sulfide melts eventually took place. The mineral potential of Offset and embayment structures appears to be empirically linked to the thickness of the overlying noritic rocks; for example, the most heavily mineralized embayments and Offset Dykes are located in areas where the Felsic Norite is thickest. It appears unlikely that the entire 1–3 km-thick melt sheet was convectively mixing throughout its lateral extent, and so the heterogeneity in sulfide distribution was retained after crystallization and cooling.